THE IMPACT OF INTELLECTUAL CAPITAL AND GOOD CORPORATE GOVERNANCE ON THE ISLAMIC BANKS' FINANCIAL PERFORMANCE: THE MODERATING ROLE OF COMPETITIVE ADVANTAGE - Annisa, Annisa; Haryono, Slamet (JURNAL AKUNTANSI DAN AUDITING, 2023)
The inconsistency of previous research results encourages this research. This study examines the impact of intellectual capital and good corporate governance on the financial performance of Islamic commercial banks moderated by competitive advantage. From 2016 to 2021, 9 Indonesian Islamic commercial banks were tested, which were selected using purposive sampling technique and estimated using panel data regression fixed effect model through Eviews 12 program. The results of this study reveal that intellectual capital can affect financial performance, but good corporate governance has no impact on the financial performance of Islamic commercial banks.  This study also reveals the relationship between intellectual capital and good corporate governance with financial performance cannot be moderated by competitive advantage. The results of this study imply the importance of managing intellectual capital to improve financial performance and the implementation of good corporate governance needs to be improved.